Ethnic and sex differences in corneal nerves and corneal epithelial cells in healthy population - Liu, Fengyi; Liu, Chang; Yu, Mingyi; Lee, Isabelle Xin Yu; Mansoor, Hassan; Cheng, Ching-Yu; Khan, Wajid Ali; Mehta, Jodhbir S.; Liu, Yu-Chi (Frontiers in Medicine, 2025)
PurposeWe aim to investigate the ethnic and sex differences in corneal nerves and epithelial cell metrics among healthy Chinese and Indian populations.MethodsThis cross-sectional study included 15,850 corneal nerve and 9,510 corneal epithelial cell images from 328 individuals, categorized into Chinese and Indian ethnicities. In-vivo confocal microscopy scans were performed to evaluate corneal nerves and epithelium. Quantitative analytic software was used to obtain 10 corneal nerve and epithelial parameters.ResultsThere were 208 Chinese participants (101 males, 107 females) in this study with a mean age of 57.0 ± 15.6 years, and 120 Indian participants (58 males, 62 females) with a mean age of 55.8 ± 21.2 years (p = 0.36). Compared to Chinese participants, Indian participants exhibited significantly higher values in all nerve parameters, including corneal nerve fiber length, fiber density, branch density, total branch density, fiber area (all p < 0.001), fiber width (p = 0.041), and fiber fractal dimension (p < 0.001). Chinese participants demonstrated significantly larger epithelial size compared to their Indian counterparts (p < 0.001). Within the Chinese cohort, females presented with significantly higher corneal nerve fiber length, fiber area, and fractal dimension than males (p = 0.034, p = 0.022 and p = 0.033, respectively). Indian females showed higher epithelial cell circularity compared to Indian males (p = 0.026).ConclusionOur study identifies significant ethnic and sex disparities in corneal nerves and epithelium. These should be considered when evaluating corneal metrics in Chinese and Indian populations.